"Improving" food processing skills by creating new entrepreneurs - Sungkawati, Endang; Usmiyatun, Usmiyatun; Karim, Samuel (Revenue Journal: Management and Entrepreneurship, 2023)
Each community has unique needs that must be met, including clothing, food and shelter. Among these three basic needs, the need for food has the highest urgency and must be met with an adequate nutritional composition to support optimal health. This research aims to increase individual knowledge and skills, especially in semi-finished food production, in order to encourage the development of entrepreneurial individuals who can apply the entrepreneurial mindset and skills they have learned during higher education and then share these abilities with the wider community. This research uses problem solving strategies to examine the process of establishing a business, especially in the food industry. The research method involves data collection techniques such as in-depth interviews and periodic monitoring. Data analysis was carried out using the SWOT analysis method. The research results showed a significant increase in participants' knowledge and motivation regarding new business founding strategies. Additionally, they gain an in-depth understanding of effective food processing techniques for long-term storage while maintaining nutritional quality. Furthermore, the community demonstrated the ability to store and process food in accordance with quality standards set by the governmen.